Paradigma Pedagogi Kritis Paulo Freire dalam Konteks Model Pendidikan yang Adaptif terhadap Masyarakat Multikultural - Ni Nyoman Putri Nursanti; Sangputri Sidik; Intan Metrayani Sidauruk (Jurnal Panrita, 2026)
This study examines the role of Paulo Freire's critical pedagogy as a basis for designing an educational model capable of adapting to the character of a multicultural society. It was conducted through a qualitative approach using a systematic literature review of scholarly publications with active DOIs published between 2020 and 2025. The author collected, selected, and analyzed literature from indexed national and international journals, then grouped the findings into core themes. The results indicate that critical pedagogy treats education as a practice of liberation that rejects the banking style of teaching and places dialogue, problem-posing, and critical awareness at the heart of learning. An adaptive multicultural education model rests on three pillars, namely recognition of learners' cultural experiences and identities, an egalitarian dialogical relationship between educator and learner, and a learning orientation directed toward social transformation for justice. The educator serves as a facilitator who presents existential problems so that learners construct a critical viewpoint on the reality of racial, ethnic, religious, and class diversity. The study concludes that the relevance of Freire's thought for Indonesian multicultural education stems from its capacity to weave together three dialectical elements of learning, namely educator, learner, and social reality, so that education functions to strengthen democracy and social cohesion in a plural society.